Self-healing full-spectrum self-adaptive flexible phase change material and preparation method thereof
By adding specific components and controlling stirring parameters during the preparation of flexible phase change materials, the problem of deterioration of toughness and uneven stirring during winter and summer conversion is solved, and the self-healing and full-spectral performance of the material is achieved.
Patent Information
- Application Number
- CN202411879655.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the prior art, the problem of deterioration of toughness of flexible phase change materials during winter and summer conversion, resulting in fracture, and uneven stirring leads to incomplete paraffin phase change.
By heating and stirring the paraffin, linear tri-embedded copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder or carbon nanotube powder are added, the initial stirring acceleration, pouring speed and height of the agitator are controlled, and the radiation cooling side film and the photo-heat conversion side film are formed, and they are pressed into the finished flexible phase change material.
The self-healing properties of the material are achieved, the toughness and durability of the material are improved, and the performance degradation and fracture of traditional materials during the winter and summer conversion process is avoided. At the same time, the full spectrum radiation cooling and photothermal conversion capabilities are also provided.
Smart Images

Figure CN119899639A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible phase change material preparation, and in particular to a self-healing full-spectrum adaptive flexible phase change material and a preparation method thereof. Background Art
[0002] In the existing technology, buildings consume a large amount of fossil fuels every year to meet people's demand for heating and cooling, and with the improvement of living standards, building energy consumption is still increasing. It is urgent to use renewable energy technology to reduce the application of fossil energy. Passive buildings using latent heat storage systems are a good way. Phase change materials (PCM) balance energy demand by absorbing or releasing latent heat during melting or solidification, compensate for the difference between energy demand and supply, and reduce energy consumption. In addition, since the temperature remains constant during the phase change of PCM, the indoor temperature can be maintained within the set temperature range, reducing indoor air temperature fluctuations and improving people's comfort. Most of the energy is consumed through the building envelope. The roof is exposed to the highest intensity and longest duration of solar radiation, so integrating PCM into the roof will face a worse working environment than integrating PCM into the wall. In summer, sky radiation cooling does not require any energy consumption and can transfer heat to the atmosphere outside the 8-13μm atmospheric window with a temperature of only 3K. However, traditional radiation cooling phase change materials are limited to improving the emissivity at the atmospheric window, so they will fail under high-intensity sunlight during the day. At the same time, this cooling technology will increase the cooling load in winter, which will have an adverse effect on heating. Solar energy, as an almost cost-free, clean, environmentally friendly, inexhaustible energy source, can be converted into heat and electricity in winter to alleviate heating needs, but its application in summer will increase the cooling load. Current materials cannot meet the needs of cooling in summer and heating in winter at the same time, and traditional PCM has no self-repair ability and lacks flexibility, and cannot roll up the sky radiation cooling material and photothermal conversion material separately for conversion.
[0003] Chinese Patent Publication No.: CN115433551A discloses a method for preparing a flexible phase-change composite material, characterized in that it comprises the following steps: Step 1, preparing Picker ing emulsion: mixing nanocellulose, thermal conductive filler, acrylamide, ferroferric oxide and antifreeze agent to obtain a uniform aqueous dispersion, mixing with paraffin wax according to different water-oil volume ratios, and obtaining Picker ing emulsion after high-speed shearing; Step 2, preparing a flexible phase-change composite material: adding an initiator and a cross-linking agent, and polymerizing the acrylamide in the Picker ing emulsion under ultraviolet light to obtain a phase-change composite material. It can be seen that the method for preparing the flexible phase-change composite material has the problems of decreased toughness and subsequent fracture due to the transition from winter to summer, and incomplete phase change of paraffin wax due to uneven stirring. Summary of the invention
[0004] To this end, the present invention provides a self-healing full-spectrum adaptive flexible phase change material and a preparation method thereof, so as to overcome the problems in the prior art of reduced toughness and subsequent breakage due to the transition from winter to summer, and incomplete paraffin phase change due to uneven stirring.
[0005] To achieve the above object, the present invention provides a method for preparing a self-healing full-spectrum adaptive flexible phase change material, comprising:
[0006] Heating paraffin to form molten paraffin, sequentially adding the linear triblock copolymer to the molten paraffin and stirring at a constant temperature and speed to form a paraffin mixture;
[0007] collecting the maximum pressure of the paraffin mixture on the stirring blades of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure;
[0008] Controlling the stirrer to stir the paraffin mixture to which the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder are added respectively according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively;
[0009] The adjustment method is determined according to the rotation speed of the stirring blade, including adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder,
[0010] Or, the pouring speed and pouring height of the corresponding initial mixed material are adjusted according to the temperature difference of the corresponding stirring blade in the vertical direction;
[0011] Pour the corresponding initial mixed materials into a press mold according to the adjustment method to press into a radiation cooling side film and a light-heat conversion side film;
[0012] The radiation cooling side film and the photothermal conversion side film laid flat on the electric heating plate are heated respectively to form a phase-changed radiation cooling side film and a phase-changed photothermal conversion side film respectively;
[0013] Wherein, the heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing;
[0014] The post-phase-change radiation cooling side film and the post-phase-change light-to-heat conversion side film are attached along the thin side edges to form a finished flexible phase-change material.
[0015] Further, the collecting of the maximum pressure of the paraffin mixture on the stirring blades of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure, comprises:
[0016] collecting the pressure per unit height of the stirring blade in the vertical direction when the paraffin mixture is stirred;
[0017] Obtaining the maximum pressure of the stirring blade;
[0018] If the maximum pressure is greater than or equal to the preset pressure, it is determined that the stirring uniformity of the paraffin mixture does not meet the requirements, and the initial stirring acceleration of the stirrer is increased.
[0019] Furthermore, the initial stirring acceleration is positively correlated with the maximum pressure.
[0020] Further, the controlling the stirrer to stir the paraffin mixture respectively added with the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively, comprises:
[0021] adding vinylidene fluoride-co-hexafluoropropylene polymer powder and carbon nanotube powder to the paraffin mixture respectively;
[0022] Start the mixer and start stirring according to the initial stirring acceleration;
[0023] After the stirring speed of the stirrer reaches a preset speed, stirring is performed at a constant temperature and constant speed according to the preset speed;
[0024] The first initial mixture and the second initial mixture are obtained respectively.
[0025] Further, the pouring speed and pouring height of the corresponding initial mixed material are adjusted according to the temperature difference of the corresponding stirring blade in the vertical direction, including:
[0026] Acquiring a first temperature of a stirring blade close to a side of the contact surface between the paraffin mixture and the air and a second temperature of a stirring blade far from a side of the contact surface between the paraffin mixture and the air;
[0027] Calculating the difference between the second temperature and the first temperature and recording the difference as the temperature difference in the vertical direction of the corresponding stirring blade in the mixer;
[0028] If the temperature difference is greater than or equal to the preset temperature difference, it is determined that the thermal efficiency of the initial mixture does not meet the requirements, and the pouring speed is reduced and the pouring height is increased at the same time.
[0029] Among them, the second temperature is greater than the first temperature, the dumping speed is negatively correlated with the temperature difference; the dumping height is positively correlated with the temperature difference.
[0030] Further, adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder comprises:
[0031] comparing the rotation speed of the stirring blade with a preset rotation speed;
[0032] If the rotation speed is less than the preset rotation speed, it is determined that the toughness of the paraffin mixture does not meet the requirement, and a horizontal rotation area of the stirring blade in the paraffin mixture corresponding to the rotation speed being greater than or equal to the preset rotation speed is obtained;
[0033] The horizontal rotation region is recorded as the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder.
[0034] Furthermore, the heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing, including:
[0035] Respectively obtaining the reduction ratio of the flattening area of the radiation cooling side film and the light-to-heat conversion side film on the electric heating plate per unit heating time;
[0036] If the reduction ratio of the tiling area is greater than or equal to a preset ratio, it is determined that the heating uniformity of the film surface does not meet the requirements, and the heating temperature of the edge area of the electric heating plate is increased.
[0037] Furthermore, the reduction ratio of the tiling area is: the ratio of the difference between the tiling area corresponding to the start time of the unit heating time and the tiling area corresponding to the end time of the unit heating time to the tiling area corresponding to the start time of the unit heating time.
[0038] Furthermore, the heating temperature of the edge area of the electric heating plate is positively correlated with the reduction ratio of the tiling area.
[0039] The present invention also provides a self-healing full-spectrum adaptive flexible phase change material, comprising: the full-spectrum adaptive flexible phase change material is a double-layer film, consisting of a radiation cooling side film and a light-heat conversion side film,
[0040] The components of the radiation cooling side film are paraffin wax, linear triblock copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder; the components of the photothermal conversion side film are paraffin wax, linear triblock copolymer and carbon nanotubes;
[0041] The ratio of the film on the radiation cooling side satisfies that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the vinylidene fluoride-co-hexafluoropropylene polymer is 100 parts, wherein the mass parts of each component are 48 parts to 80 parts of paraffin, 12 parts to 20 parts of the linear triblock copolymer, and 0 parts to 40 parts of the vinylidene fluoride-co-hexafluoropropylene polymer;
[0042] The ratio of the light-to-heat conversion side film is such that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the carbon nanotubes is 100 parts, wherein the mass parts of each component are 71 parts to 80 parts of paraffin, 17 parts to 20 parts of the linear triblock copolymer, and 0 parts to 12 parts of the carbon nanotubes;
[0043] The thickness of the film on the radiation cooling side is 2 mm, and the thickness of the film on the light-to-heat conversion side is 2 mm.
[0044] Compared with the prior art, the beneficial effect of the present invention lies in that the method of the present invention forms the radiation cooling side of the flexible phase change material through paraffin, linear triblock copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder, and forms the photothermal conversion side through paraffin, linear triblock copolymer and carbon nanotube powder, thereby realizing the self-healing property of the material, improving the toughness and durability of the material, and preventing the performance degradation and fracture of the traditional material during the winter-summer conversion process; the material of the present invention can not only adapt to the full-spectrum radiation cooling and photothermal conversion, but also has self-healing ability; by controlling the stirring acceleration, pouring speed and pouring height, as well as the heating time long, ensuring the uniformity and thermal efficiency of the material; since the paraffin is continuously heated and stirred during the preparation process, the stirring stress continuously affects the paraffin during the stirring process, resulting in increased viscosity of the paraffin and thus uneven stirring, and due to the poor thermal conductivity of the paraffin mixture, the temperature difference of the initial mixture in the vertical direction is too large, resulting in different phase change uniformity at different positions of the pressed film. The stirring uniformity is increased by adjusting the initial stirring acceleration, and the contact area between the mixture and the air is increased by adjusting the pouring speed and pouring height, thereby reducing the temperature difference, thereby achieving an improvement in preparation efficiency and reducing the decline in material performance stability caused by temperature fluctuations.
[0045] Furthermore, the method of the present invention sets a preset pressure. During the stirring process, the toughness of the paraffin increases, thereby increasing the pressure on the stirring blades. The tough paraffin has strong adhesion, so the stirring uniformity is reduced. By increasing the initial stirring acceleration of the subsequent mixer, the shear stress on the paraffin is increased, and the laminar state of the paraffin caused by the stirring is destroyed, thereby improving the stirring efficiency, achieving improved stirring fluidity and increased dispersion, and further achieving improved stirring uniformity.
[0046] Furthermore, the method of the present invention sets a preset temperature difference. Before being pressed into a film, the temperature difference at each height in the vertical direction in the mixture is too large and the thermal efficiency is low, which causes uneven thermal stress inside the mixture. The poured mixture has large temperature fluctuations in each part, resulting in decreased material property stability and uneven phase change. By reducing the pouring speed and increasing the pouring height, the contact area and contact time between the mixture and the air are increased, and the temperature difference between the mixture is reduced, thereby achieving an increase in material property stability.
[0047] Furthermore, the material of the present invention uses paraffin as the main phase change material, and its use on the radiation cooling side and the photothermal conversion side can effectively store and release heat, thereby achieving the purpose of regulating temperature; the melting point and freezing point of paraffin make it have good phase change performance within the daily temperature range; by adding linear triblock copolymers, not only the mechanical strength of the material is improved, but also its thermal stability is enhanced. The structural design of the linear triblock copolymer enables it to form a stable composite material with paraffin and poly or carbon nanotubes, thereby maintaining the structural integrity of the material while improving thermal efficiency; in the radiation cooling side film, the appropriate addition of vinylidene fluoride-co-hexafluoropropylene polymer can further improve the radiation cooling ability of the material, and the poly material has a high emissivity and can effectively release the absorbed heat to the outside in the form of infrared radiation, thereby reducing the temperature of the material surface; in the photothermal conversion side film, the introduction of carbon nanotubes improves the photothermal conversion efficiency of the material; carbon nanotubes have excellent photoelectric conversion performance and can efficiently convert the absorbed light energy into heat energy, thereby rapidly increasing the temperature of the material under lighting conditions, thereby increasing the room temperature flexibility of the flexible phase change material. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is an overall flow chart of a method for preparing a self-healing full-spectrum adaptive flexible phase change material according to an embodiment of the present invention;
[0049] Figure 2 This is a structural diagram of a self-healing full-spectrum adaptive flexible phase change material according to an embodiment of the present invention;
[0050] Figure 3 This is a stress-strain curve diagram of the self-healing full-spectrum adaptive flexible phase change material of Example 11 of the present invention;
[0051] Figure 4 The stress-strain curve diagram of the radiation cooling side film and the photothermal conversion side film of the self-healing full-spectrum adaptive flexible phase change material of Example 12 of the present invention after self-healing;
[0052] Figure 5 This is a differential scanning quantification curve diagram of the self-healing full-spectrum adaptive flexible phase change material of Example 11 of the present invention;
[0053] Figure 6 This is a solar light band reflectivity diagram of the radiation cooling side film of the self-healing full-spectrum adaptive flexible phase change material of Example 11 of the present invention;
[0054] Figure 7 This is a solar light band transmittance diagram of the radiation cooling side film of the self-healing full-spectrum adaptive flexible phase change material of Example 11 of the present invention;
[0055] Figure 8 This is a photothermal conversion diagram of a photothermal conversion side film of a self-healing full-spectrum adaptive flexible phase change material according to Example 11 of the present invention;
[0056] Explanation of the accompanying figures: 1-radiative cooling side film, 2-photothermal conversion side film, 3-curve before phase change, 4-curve after phase change. DETAILED DESCRIPTION
[0057] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0059] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0060] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0061] See also Figure 1 and Figure 2As shown. They are respectively an overall flow chart of the preparation method of the self-healing full-spectrum adaptive flexible phase change material of the embodiment and a structural diagram of the self-healing full-spectrum adaptive flexible phase change material of the embodiment. A preparation method of a self-healing full-spectrum adaptive flexible phase change material of the embodiment of the present invention comprises:
[0062] Step S1, heating paraffin to form molten paraffin, sequentially adding linear triblock copolymers into the molten paraffin and stirring at a constant temperature and speed to form a paraffin mixture;
[0063] Step S2, collecting the maximum pressure of the paraffin mixture on the stirring blade of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure;
[0064] Step S3, controlling the stirrer to stir the paraffin mixture to which the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder are added respectively according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively;
[0065] Step S4, determining an adjustment method according to the rotation speed of the stirring blade, including adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder,
[0066] Or, the pouring speed and pouring height of the corresponding initial mixed material are adjusted according to the temperature difference of the corresponding stirring blade in the vertical direction;
[0067] Step S5, pouring the corresponding initial mixed material into a press mold according to the adjustment method to press into a radiation cooling side film and a light-to-heat conversion side film;
[0068] Step S6, heating the radiation cooling side film and the photothermal conversion side film laid on the electric heating plate respectively to form a phase-changed radiation cooling side film and a phase-changed photothermal conversion side film respectively;
[0069] Wherein, the heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing;
[0070] Step S7, laminating the post-phase-change radiation cooling side film and the post-phase-change light-to-heat conversion side film along the thin side edges to form a finished flexible phase-change material.
[0071] Specifically, the stirring device described in the present invention can be an electric lifting stirrer for paraffin mixing and stirring, a magnetic stirrer and a temperature-controlled stirrer. The preferred embodiment of the stirring device described in the present invention is a temperature-controlled stirrer.
[0072] Specifically, a plurality of pressure sensors and a plurality of temperature sensors are arranged on the contact surface between the stirring device and the material.
[0073] Specifically, the electric heating plate described in the present invention can be a temperature-controlled electric heating plate or a digital display electric heating plate. The preferred embodiment of the electric heating plate described in the present invention is a temperature-controlled electric heating plate.
[0074] Specifically, in step S2, the mass ratio of paraffin wax to the linear triblock copolymer generally ranges from [3:1, 5:1], and the preferred embodiment of the mass ratio of paraffin wax to the linear triblock copolymer is 4:1.
[0075] Specifically, in step S2, the general value range of the stirring temperature is [125°C, 135°C], the general value range of the stirring speed is [55r / min, 65r / min], and the general value range of the stirring time is [0.4 hour, 0.6 hour]; preferably, the preferred embodiment of the stirring temperature is 130°C, the preferred embodiment of the stirring speed is 60r / min, and the preferred embodiment of the stirring time is 0.5 hour.
[0076] Specifically, the vinylidene fluoride-co-hexafluoropropylene polymer powder is a vinylidene fluoride-co-hexafluoropropylene powder.
[0077] Specifically, in step S4, the general value range of the stirring time is [8 minutes, 12 minutes]; the preferred embodiment of the stirring time is 10 minutes.
[0078] Specifically, in step S9, the general value range of the laminating time is [4.5 minutes, 6 minutes]; the preferred embodiment of the laminating time is 5 minutes.
[0079] In practice, the method of the present invention uses paraffin, linear triblock copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder to form the radiation cooling side of the flexible phase change material, and uses paraffin, linear triblock copolymer and carbon nanotube powder to form the photothermal conversion side, thereby realizing the self-healing property of the material and improving the toughness and durability of the material. The performance degradation and fracture of traditional materials during the winter-summer conversion process are avoided. The material of the present invention can not only adapt to the full-spectrum radiation cooling and photothermal conversion, but also has self-healing ability. By controlling the stirring acceleration, pouring speed and pouring height, as well as the heating time, the material is ensured. uniformity and thermal efficiency; since the paraffin is continuously heated and stirred during the preparation process, the stirring stress continuously affects the paraffin during the stirring process, which increases the viscosity of the paraffin and leads to uneven stirring, and the thermal conductivity of the paraffin mixture is poor, resulting in excessive temperature difference in the vertical direction of the initial mixture, resulting in different phase change uniformity at different positions of the pressed film. The stirring uniformity is increased by adjusting the initial stirring acceleration, and the contact area between the mixture and the air is increased by adjusting the pouring speed and pouring height, thereby reducing the temperature difference, thereby improving the preparation efficiency and reducing the decline in material performance stability caused by temperature fluctuations.
[0080] Specifically, the collecting of the maximum pressure of the paraffin mixture on the stirring blade of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure, comprises:
[0081] collecting the pressure per unit height of the stirring blade in the vertical direction when the paraffin mixture is stirred;
[0082] Obtaining the maximum pressure of the stirring blade;
[0083] If the maximum pressure is greater than or equal to the preset pressure, it is determined that the stirring uniformity of the paraffin mixture does not meet the requirements, and the initial stirring acceleration of the stirrer is increased.
[0084] Specifically, the initial stirring acceleration is positively correlated with the maximum pressure.
[0085] Specifically, the general value range of the preset pressure is [0.6N, 0.8N].
[0086] Preferably, the preset pressure is 0.7N.
[0087] In practice, when the difference between the maximum pressure and the preset pressure is within 0.1N, the initial stirring acceleration is increased by 10r / min. 2 , the difference between the maximum pressure and the preset pressure exceeds 0.1N, and the initial stirring acceleration increases by 10r / min for every 0.1N difference. 2; For example, the maximum pressure is 1N, the current initial stirring acceleration increases to 120r / min 2 , the initial stirring acceleration increases to 120r / min 2 +10r / min 2 +10r / min 2 ×2=150r / min 2 .
[0088] In implementation, the method of the present invention sets a preset pressure. During the stirring process, the toughness of the paraffin increases, thereby increasing the pressure on the stirring blades. The tough paraffin has strong adhesion, so the stirring uniformity is reduced. By increasing the initial stirring acceleration of the subsequent mixer, the shear stress on the paraffin is increased, and the laminar state of the paraffin caused by the stirring is destroyed, thereby improving the stirring efficiency, achieving improved stirring fluidity and increased dispersion, and further achieving improved stirring uniformity.
[0089] Specifically, the controlling the stirrer to stir the paraffin mixture respectively added with the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively, comprises:
[0090] adding vinylidene fluoride-co-hexafluoropropylene polymer powder and carbon nanotube powder to the paraffin mixture respectively;
[0091] Start the mixer and start stirring according to the initial stirring acceleration;
[0092] After the stirring speed of the stirrer reaches a preset speed, stirring is performed at a constant temperature and constant speed according to the preset speed;
[0093] The first initial mixture and the second initial mixture are obtained respectively.
[0094] Specifically, the general value range of the preset speed is [55r / min, 65r / min], and the preferred embodiment of the preset speed is 60r / min.
[0095] Specifically, the pouring speed and pouring height of the corresponding initial mixed material are adjusted according to the temperature difference of the corresponding stirring blade in the vertical direction, including:
[0096] Acquiring a first temperature of a stirring blade close to a side of the contact surface between the paraffin mixture and the air and a second temperature of a stirring blade far from a side of the contact surface between the paraffin mixture and the air;
[0097] Calculating the difference between the second temperature and the first temperature and recording the difference as the temperature difference in the vertical direction of the corresponding stirring blade in the mixer;
[0098] If the temperature difference is greater than or equal to the preset temperature difference, it is determined that the thermal efficiency of the initial mixture does not meet the requirements, and the pouring speed is reduced and the pouring height is increased at the same time.
[0099] Among them, the second temperature is greater than the first temperature, the dumping speed is negatively correlated with the temperature difference; the dumping height is positively correlated with the temperature difference.
[0100] Specifically, the pouring speed and pouring height are regulated by a pouring fixture connected to a loading container of the initial mix.
[0101] Specifically, the general value range of the preset temperature difference is [0.12°C / cm, 0.16°C / cm].
[0102] Preferably, the preset temperature difference is 0.15°C / cm.
[0103] In practice, if the temperature difference per unit height is within 0.02℃ / cm from the preset temperature difference, the pouring speed will be reduced by 30cm. 3 / min, the pouring height increases by 4cm; if the difference between the unit height temperature difference and the preset temperature difference exceeds 0.02℃ / cm, the pouring speed decreases by 50cm for every 0.02℃ / cm 3 / min, the dumping height increases by 4cm; for example, the temperature difference per unit height is 0.17℃ / cm, and the current dumping speed is 500cm 3 / min, the dumping height is 30cm, then the dumping speed is reduced to 500cm 3 / min-30cm 3 / min-50cm 3 / min=420cm 3 / min, the dumping height increases to 30cm+4cm+4cm=38cm.
[0104] In practice, the method of the present invention sets a preset temperature difference. Before being pressed into a film, the temperature difference at each height in the vertical direction in the mixture is too large and the thermal efficiency is low, which causes uneven thermal stress inside the mixture. The poured mixture has large temperature fluctuations in each part, resulting in decreased material property stability and uneven phase change. By reducing the pouring speed and increasing the pouring height, the contact area and contact time between the mixture and the air are increased, and the temperature difference between the mixture is reduced, thereby achieving an increase in material property stability.
[0105] Specifically, adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder includes:
[0106] comparing the rotation speed of the stirring blade with a preset rotation speed;
[0107] If the rotation speed is less than the preset rotation speed, it is determined that the toughness of the paraffin mixture does not meet the requirement, and a horizontal rotation area of the stirring blade in the paraffin mixture corresponding to the rotation speed being greater than or equal to the preset rotation speed is obtained;
[0108] The horizontal rotation region is recorded as the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder.
[0109] Specifically, the general value range of the preset speed is [8r / min, 14r / min], and the preferred embodiment of the preset speed is 10r / min.
[0110] Specifically, the heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing, including:
[0111] Respectively obtaining the reduction ratio of the flattening area of the radiation cooling side film and the light-to-heat conversion side film on the electric heating plate per unit heating time;
[0112] If the reduction ratio of the tiling area is greater than or equal to a preset ratio, it is determined that the heating uniformity of the film surface does not meet the requirements, and the heating temperature of the edge area of the electric heating plate is increased.
[0113] Specifically, the reduction ratio of the tiling area is the ratio of the difference between the tiling area corresponding to the start time of the unit heating time and the tiling area corresponding to the end time of the unit heating time to the tiling area corresponding to the start time of the unit heating time.
[0114] Specifically, the heating temperature of the edge area of the electric heating plate is positively correlated with the reduction ratio of the tiling area.
[0115] Specifically, the devices for measuring the paving area of the radiation cooling side film and the photothermal conversion side film are industrial cameras and infrared rangefinders, and the preferred embodiment of the flatness measuring device is an infrared rangefinder.
[0116] Specifically, the edge area of the electric heating plate is a reduced area of the flat surface of the radiation cooling side film and the light-to-heat conversion side film.
[0117] Specifically, the general value range of the preset ratio is [0.01, 0.02].
[0118] Preferably, the preferred embodiment of the preset ratio is 0.014.
[0119] During implementation, when the difference between the reduction ratio of the tiling area and the preset ratio is within 0.002, the heating temperature increases by 0.4°C; when the difference between the reduction ratio of the tiling area and the preset ratio exceeds 0.002, the heating temperature increases by 0.5°C for every 0.005 exceeding it; for example, when the reduction ratio of the tiling area is 50μm and the current heating temperature is 60°C, the heating temperature increases to 60°C+0.4°C+0.5°C=60.9°C.
[0120] The embodiment of the present invention further provides a self-healing full-spectrum adaptive flexible phase change material, comprising: the full-spectrum adaptive flexible phase change material is a double-layer film, consisting of a radiation cooling side film and a light-heat conversion side film,
[0121] The components of the radiation cooling side film are paraffin wax, linear triblock copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder; the components of the photothermal conversion side film are paraffin wax, linear triblock copolymer and carbon nanotubes;
[0122] The ratio of the film on the radiation cooling side satisfies that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the vinylidene fluoride-co-hexafluoropropylene polymer is 100 parts, wherein the mass parts of each component are 48 parts to 80 parts of paraffin, 12 parts to 20 parts of the linear triblock copolymer, and 0 parts to 40 parts of the vinylidene fluoride-co-hexafluoropropylene polymer;
[0123] The ratio of the light-to-heat conversion side film is such that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the carbon nanotubes is 100 parts, wherein the mass parts of each component are 71 parts to 80 parts of paraffin, 17 parts to 20 parts of the linear triblock copolymer, and 0 parts to 12 parts of the carbon nanotubes;
[0124] The thickness of the film on the radiation cooling side is 2 mm, and the thickness of the film on the light-to-heat conversion side is 2 mm.
[0125] In practice, the material of the present invention uses paraffin as the main phase change material, and its use on the radiation cooling side and the photothermal conversion side can effectively store and release heat, thereby achieving the purpose of regulating temperature; the melting point and freezing point of paraffin make it have good phase change performance within the daily temperature range; by adding linear triblock copolymers, not only the mechanical strength of the material is improved, but also its thermal stability is enhanced. The structural design of the linear triblock copolymer enables it to form a stable composite material with paraffin and poly or carbon nanotubes, thereby maintaining the structural integrity of the material while improving thermal efficiency; in the radiation cooling side film, the appropriate addition of vinylidene fluoride-co-hexafluoropropylene polymer can further improve the radiation cooling ability of the material, and the poly material has a high emissivity and can effectively release the absorbed heat to the outside in the form of infrared radiation, thereby reducing the temperature of the material surface; in the photothermal conversion side film, the introduction of carbon nanotubes improves the photothermal conversion efficiency of the material; carbon nanotubes have excellent photoelectric conversion performance and can efficiently convert the absorbed light energy into heat energy, thereby rapidly increasing the temperature of the material under light conditions, thereby increasing the room temperature flexibility of the flexible phase change material.
[0126] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described in conjunction with the following examples; it should be understood that the specific examples described herein are only used to explain the present invention and are not used to limit the present invention.
[0127] Embodiment 1:
[0128] Take out 90 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 10 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 96 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 4 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0129] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 157.08 kJ / kg; the solar reflectivity before the phase change is 63.98%, the solar transmittance before the phase change is 20.39%, the solar reflectivity after the phase change is 14.88%, the solar transmittance after the phase change is 61.09%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 168.28 kJ / kg; the photothermal conversion efficiency is 91.11%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0130] Embodiment 2:
[0131] Take out 90 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 10 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 92 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 8 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0132] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 157.08 kJ / kg; the solar reflectivity before the phase change is 63.98%, the solar transmittance before the phase change is 20.39%, the solar reflectivity after the phase change is 14.88%, the solar transmittance after the phase change is 61.09%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 161.34 kJ / kg; the photothermal conversion efficiency is 93.23%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0133] Embodiment 3:
[0134] Take out 90 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 10 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 88 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 12 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0135] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 157.08 kJ / kg; the solar reflectivity before the phase change is 63.98%, the solar transmittance before the phase change is 20.39%, the solar reflectivity after the phase change is 14.88%, the solar transmittance after the phase change is 61.09%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 156.13 kJ / kg; the photothermal conversion efficiency is 91.24%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0136] Embodiment 4:
[0137] Take out 80 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 20 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 96 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 4 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0138] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 142.21 kJ / kg; the solar reflectivity before the phase change is 65.48%, the solar transmittance before the phase change is 19.28%, the solar reflectivity after the phase change is 22.88%, the solar transmittance after the phase change is 50.62%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 168.28 kJ / kg; the photothermal conversion efficiency is 91.11%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0139] Embodiment 5:
[0140] Take out 80 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 20 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 92 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 8 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0141] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 142.21 kJ / kg; the solar reflectivity before the phase change is 65.48%, the solar transmittance before the phase change is 19.28%, the solar reflectivity after the phase change is 22.88%, the solar transmittance after the phase change is 50.62%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 161.34 kJ / kg; the photothermal conversion efficiency is 93.23%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0142] Embodiment 6:
[0143] Take out 80 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 20 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 88 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 12 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0144] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 142.21 kJ / kg; the solar reflectivity before the phase change is 65.48%, the solar transmittance before the phase change is 19.28%, the solar reflectivity after the phase change is 22.88%, the solar transmittance after the phase change is 50.62%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 156.13 kJ / kg; the photothermal conversion efficiency is 91.24%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0145] Embodiment 7:
[0146] Take out 70 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 30 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 96 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 4 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0147] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 122.82 kJ / kg; the solar reflectivity before the phase change is 72.76%, the solar transmittance before the phase change is 13.99%, the solar reflectivity after the phase change is 29.79%, the solar transmittance after the phase change is 46.49%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 168.28 kJ / kg; the photothermal conversion efficiency is 91.11%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0148] Embodiment 8:
[0149] Take out 70 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 30 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 92 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 8 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0150] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 122.82 kJ / kg; the solar reflectivity before the phase change is 72.76%, the solar transmittance before the phase change is 13.99%, the solar reflectivity after the phase change is 29.79%, the solar transmittance after the phase change is 46.49%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 161.34 kJ / kg; the photothermal conversion efficiency is 93.23%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0151] Embodiment 9:
[0152] Take out 70 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 30 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 88 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 12 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0153] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 122.82 kJ / kg; the solar reflectivity before the phase change is 72.76%, the solar transmittance before the phase change is 13.99%, the solar reflectivity after the phase change is 29.79%, the solar transmittance after the phase change is 46.49%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 156.13 kJ / kg; the photothermal conversion efficiency is 91.24%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0154] Embodiment 10:
[0155] Take out 60 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 40 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 96 parts of the paraffin mixture of paraffin and linear tri-embedded copolymer, add 4 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0156] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of approximately 107.34 kJ / kg; the solar reflectivity before the phase change is 77.00%, the solar transmittance before the phase change is 9.77%, the solar reflectivity after the phase change is 36.94%, the solar transmittance after the phase change is 44.46%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is approximately 168.28 kJ / kg; the photothermal conversion efficiency is 91.11%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0157] Embodiment 11:
[0158] See also Figure 3 , Figure 5 , Figure 6 , Figure 7 as well as Figure 8 As shown, they are respectively a stress-strain curve diagram of the self-healing full-spectrum adaptive flexible phase change material 11 of an embodiment of the present invention, a differential scanning calorimetry curve diagram, a solar light band reflectivity diagram of the radiation cooling side film, a solar light band transmittance diagram of the radiation cooling side film, and a photothermal conversion diagram of the photothermal conversion side film.
[0159] Take out 60 parts of the paraffin wax mixture of paraffin wax and linear triblock copolymer, add 40 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at a constant temperature and speed for 10 minutes, the stirrer oil bath temperature is 130°C, the stirring speed is 60 revolutions per minute, and the radiation cooling side film is obtained by pressing. Take out 92 parts of the paraffin wax mixture of paraffin wax and linear triblock copolymer, add 8 parts of carbon nanotubes thereto, continue to stir at a constant temperature and speed for 10 minutes, the stirrer oil bath temperature is 130°C, the stirring speed is 60 revolutions per minute, and the photothermal conversion side film is obtained by pressing. The radiation cooling side film and the photothermal conversion side film are laid flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are laminated along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material. The full-spectrum adaptive flexible phase change material is subjected to stress-strain detection by magnetic measurement and a stress-strain curve diagram is obtained. The full-spectrum adaptive flexible phase change material is detected by a differential scanning calorimeter and a differential scanning calorimeter curve diagram is obtained.
[0160] Specifically, stress-strain detection and differential scanning calorimetry detection are existing technologies well known to those skilled in the art, so the detection process will not be described in detail.
[0161] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of about 107.34 kJ / kg; the solar reflectivity before the phase change is 77.00%, the solar transmittance before the phase change is 9.77%, the solar reflectivity after the phase change is 36.94%, the solar transmittance after the phase change is 44.46%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is about 161.34 kJ / kg; the photothermal conversion efficiency is 93.23%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0162] Embodiment 12:
[0163] See also Figure 4 As shown, it is a stress-strain curve diagram of the radiation cooling side film and the photothermal conversion side film of the self-healing full-spectrum adaptive flexible phase change material in Example 12 of the present invention after self-healing.
[0164] Take out 60 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 40 parts of poly (vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a radiation cooling side film, take out 88 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 12 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the oil bath temperature of the stirrer is 130°C, the stirring speed is 60 revolutions per minute, and press to obtain a photothermal conversion side film, lay the radiation cooling side film and the photothermal conversion side film flat on a temperature-controlled electric heating plate at 60°C, so that the paraffin contained in the radiation cooling side and photothermal conversion side films fully undergoes phase change, and the radiation cooling side and photothermal conversion side films are bonded along the side edges for 5 minutes to obtain a full-spectrum adaptive flexible phase change material.
[0165] The full-spectrum adaptive flexible phase change material obtained in this embodiment has a phase change enthalpy of the radiation cooling side film of about 107.34 kJ / kg; the solar reflectivity before the phase change is 77.00%, the solar transmittance before the phase change is 9.77%, the solar reflectivity after the phase change is 36.94%, the solar transmittance after the phase change is 44.46%, and the material can be bent 720° without being damaged; it has self-healing properties; the phase change enthalpy of the photothermal conversion side film is about 156.13 kJ / kg; the photothermal conversion efficiency is 91.24%; the material can be bent 720° without being damaged; it has self-healing properties, and the radiation cooling side film and the photothermal conversion side film can be bonded together by their own viscosity.
[0166] Comparative Example 1: without poly(vinylidene fluoride-co-hexafluoropropylene) and carbon nanotubes;
[0167] 100 parts of the paraffin wax mixture of the paraffin wax and the linear triblock copolymer were taken out and pressed into sheets to obtain a flexible phase change material.
[0168] The flexible phase change material obtained in this comparative example has a phase change enthalpy of about 179.80 kJ / kg; the solar reflectivity before the phase change is 50.26%, the solar transmittance before the phase change is 29.80%, the solar reflectivity after the phase change is 6.37%, the solar transmittance after the phase change is 83.27%, and the photothermal conversion efficiency is 28.28%; the material can be bent 720° without being damaged; and it has self-healing properties.
[0169] From the comparative analysis of the experimental data of Examples 1-12 and Comparative Example 3, it can be seen that without adding poly(vinylidene fluoride-co-hexafluoropropylene) and carbon nanotubes, the effects of cooling in summer and heating in winter cannot be achieved.
[0170] Comparative Example 2: without carbon nanotubes;
[0171] Take out 60 parts of the paraffin mixture of paraffin and linear triblock copolymer, add 40 parts of poly(vinylidene fluoride-co-hexafluoropropylene) thereto, continue to stir at constant temperature and speed for 10 minutes, the stirrer oil bath temperature is 130°C, the stirring speed is 60 revolutions per minute, and the flexible phase change material is obtained by tableting.
[0172] The flexible phase change material obtained in this comparative example has a phase change enthalpy of about 107.34 kJ / kg; the solar reflectivity before the phase change is 77.00%, the solar transmittance before the phase change is 9.77%, the solar reflectivity after the phase change is 36.94%, and the solar transmittance after the phase change is 44.46%; the material can be bent 720° without being damaged; and has self-healing properties.
[0173] From the comparative analysis of the experimental data of Examples 1-3, Examples 4-6, Examples 7-9, Examples 10-12 and Comparative Example 2, it can be seen that under the conditions that the preparation conditions and composition of the radiation cooling side film remain unchanged, the composition of the photothermal conversion side film is changed, specifically, the number of carbon nanotubes is increased and the number of paraffin mixture is reduced, the phase change enthalpy of the photothermal conversion side film tends to decrease, and the photothermal conversion efficiency tends to increase. Adding carbon nanotubes can achieve the effects of cooling in summer and heating in winter.
[0174] Comparative Example 3: No poly(vinylidene fluoride-co-hexafluoropropylene);
[0175] Take out 92 parts of the paraffin wax mixture of paraffin wax and linear triblock copolymer, add 8 parts of carbon nanotubes thereto, continue to stir at constant temperature and speed for 10 minutes, the stirrer oil bath temperature is 130°C, the stirring speed is 60 revolutions per minute, and press into sheets to obtain a flexible phase change material.
[0176] The flexible phase change material obtained in this comparative example has a phase change enthalpy of about 161.34 kJ / kg, a light-to-heat conversion efficiency of 93.23%, and can be bent 720° without being damaged; and has self-healing properties.
[0177] From the comparative analysis of the experimental data of Examples 1, 4, 7, 10, Examples 2, 5, 8, 11, Examples 3, 6, 9, 12 and Comparative Example 3, it can be seen that under the conditions where the preparation conditions and composition of the film on the photothermal conversion side remain unchanged, the composition of the film on the radiation cooling side is changed, specifically, the proportion of poly(vinylidene fluoride-co-hexafluoropropylene) is increased, and the proportion of the paraffin mixture is reduced. After the phase change, the solar transmittance shows an increasing trend, and the solar reflectivity shows a decreasing trend after the phase change. Adding poly(vinylidene fluoride-co-hexafluoropropylene) can achieve the effects of cooling in summer and heating in winter.
[0178] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A method for preparing a self-healing full-spectrum adaptive flexible phase change material, characterized in that: include: Heating paraffin to form molten paraffin, sequentially adding the linear triblock copolymer to the molten paraffin and stirring at a constant temperature and speed to form a paraffin mixture; collecting the maximum pressure of the paraffin mixture on the stirring blades of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure; Controlling the stirrer to stir the paraffin mixture to which the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder are added respectively according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively; The adjustment method is determined according to the rotation speed of the stirring blade, including adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder, Or, the pouring speed and pouring height of the corresponding initial mixed material are adjusted according to the temperature difference of the corresponding stirring blade in the vertical direction; Pour the corresponding initial mixed materials into a press mold according to the adjustment method to press into a radiation cooling side film and a light-heat conversion side film; The radiation cooling side film and the photothermal conversion side film laid flat on the electric heating plate are heated respectively to form a phase-changed radiation cooling side film and a phase-changed photothermal conversion side film respectively; Wherein, the heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing; The post-phase-change radiation cooling side film and the post-phase-change light-to-heat conversion side film are attached along the thin side edges to form a finished flexible phase-change material.
2. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 1, characterized in that: The step of collecting the maximum pressure of the paraffin mixture on the stirring blades of the stirrer at the moment of stopping the stirring, and determining the initial stirring acceleration of the stirrer according to the maximum pressure comprises: collecting the pressure per unit height of the stirring blade in the vertical direction when the paraffin mixture is stirred; Obtaining the maximum pressure of the stirring blade; If the maximum pressure is greater than or equal to the preset pressure, it is determined that the stirring uniformity of the paraffin mixture does not meet the requirements, and the initial stirring acceleration of the stirrer is increased.
3. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 2, characterized in that: The initial stirring acceleration is positively correlated with the maximum pressure.
4. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 3, characterized in that: The method of controlling the stirrer to stir the paraffin mixture respectively added with the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder according to the initial stirring acceleration to form a first initial mixed material and a second initial mixed material respectively, comprises: adding vinylidene fluoride-co-hexafluoropropylene polymer powder and carbon nanotube powder to the paraffin mixture respectively; Start the mixer and start stirring according to the initial stirring acceleration; After the stirring speed of the stirrer reaches a preset speed, stirring is performed at a constant temperature and constant speed according to the preset speed; The first initial mixture and the second initial mixture are obtained respectively.
5. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 4, characterized in that: The method of adjusting the pouring speed and pouring height of the corresponding initial mixed material according to the temperature difference of the corresponding stirring blade in the vertical direction comprises: Acquiring a first temperature of a stirring blade close to a side of the contact surface between the paraffin mixture and the air and a second temperature of a stirring blade far from a side of the contact surface between the paraffin mixture and the air; Calculating the difference between the second temperature and the first temperature and recording the difference as the temperature difference in the vertical direction of the corresponding stirring blade in the mixer; If the temperature difference is greater than or equal to the preset temperature difference, it is determined that the thermal efficiency of the initial mixture does not meet the requirements, and the pouring speed is reduced and the pouring height is increased at the same time. Among them, the second temperature is greater than the first temperature, the dumping speed is negatively correlated with the temperature difference; the dumping height is positively correlated with the temperature difference.
6. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 5, characterized in that: Adjusting the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder comprises: comparing the rotation speed of the stirring blade with a preset rotation speed; If the rotation speed is less than the preset rotation speed, it is determined that the toughness of the paraffin mixture does not meet the requirement, and a horizontal rotation area of the stirring blade in the paraffin mixture corresponding to the rotation speed being greater than or equal to the preset rotation speed is obtained; The horizontal rotation region is recorded as the addition range of the vinylidene fluoride-co-hexafluoropropylene polymer powder and the carbon nanotube powder.
7. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 6, characterized in that: The heating temperature of the edge area of the electric heating plate is determined according to the reduction ratio of the flattened area of each film after pressing, including: Respectively obtaining the reduction ratio of the flattening area of the radiation cooling side film and the light-to-heat conversion side film on the electric heating plate per unit heating time; If the reduction ratio of the tiling area is greater than or equal to a preset ratio, it is determined that the heating uniformity of the film surface does not meet the requirements, and the heating temperature of the edge area of the electric heating plate is increased.
8. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 7, characterized in that: The reduction ratio of the tiling area is: the ratio of the difference between the tiling area corresponding to the start time of the unit heating time and the tiling area corresponding to the end time of the unit heating time to the tiling area corresponding to the start time of the unit heating time.
9. The method for preparing the self-healing full-spectrum adaptive flexible phase change material according to claim 8, characterized in that: The heating temperature of the edge area of the electric heating plate is positively correlated with the reduction ratio of the tiling area.
10. A full-spectrum self-adaptive flexible phase change material prepared by the method for preparing a full-spectrum self-adaptive flexible phase change material based on self-healing property according to any one of claims 1 to 9, characterized in that: include: The full-spectrum adaptive flexible phase-change material is a double-layer film, consisting of a radiation cooling side film and a light-heat conversion side film. The components of the radiation cooling side film are paraffin wax, linear triblock copolymer and vinylidene fluoride-co-hexafluoropropylene polymer powder; the components of the photothermal conversion side film are paraffin wax, linear triblock copolymer and carbon nanotubes; The ratio of the film on the radiation cooling side satisfies that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the vinylidene fluoride-co-hexafluoropropylene polymer is 100 parts, wherein the mass parts of each component are 48 parts to 80 parts of paraffin, 12 parts to 20 parts of the linear triblock copolymer, and 0 parts to 40 parts of the vinylidene fluoride-co-hexafluoropropylene polymer; The ratio of the light-to-heat conversion side film is such that the sum of the mass parts of paraffin, the mass parts of the linear triblock copolymer and the mass parts of the carbon nanotubes is 100 parts, wherein the mass parts of each component are 71 parts to 80 parts of paraffin, 17 parts to 20 parts of the linear triblock copolymer, and 0 parts to 12 parts of the carbon nanotubes; The thickness of the film on the radiation cooling side is 2 mm, and the thickness of the film on the light-to-heat conversion side is 2 mm.
Citation Information
Patent Citations
Flexible phase change composite material and preparation method thereof
CN115433551A
Elastic phase-change temperature-adjusting fiber, preparation method thereof and lithium battery aluminum-plastic film temperature-adjusting bonding layer comprising elastic phase-change temperature-adjusting fiber
CN114892307A
Flexible high-emission phase change cold storage material and preparation method thereof
CN117070195A
Flexible composite phase change film capable of storing heat by using solar energy
CN117261381A
Self-cleaning energy storage flexible electrostatic film and preparation method thereof
CN118109966A